2022
DOI: 10.5194/cp-18-2271-2022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the distributions of hydroxylated glycerol dibiphytanyl glycerol tetraethers (GDGTs) in Holocene Baltic Sea sediments for reconstruction of sea surface temperature: the effect of changing salinity

Abstract: Abstract. Hydroxylated glycerol dibiphytanyl glycerol tetraethers (OH-GDGTs) produced by both marine and freshwater thaumarchaea are increasingly used for the reconstruction of past sea surface temperature (SST). They occur throughout the modern Baltic Sea, but it is unknown if OH-GDGTs can be used for assessing past SST in this area, where salinity has changed considerably over the Holocene. Three commonly applied OH-GDGT proxies for SST reconstruction, i.e., the OH-GDGT%, RI-OH, and RI-OH′ indices, were test… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In addition to temperature, recent studies have shown that several other environmental and geochemical factors can influence the degree of GDGT cyclization, such as growth phase (Elling et al, 2014), ammonia oxidation rates (Hurley et al, 2016), and oxygen concentrations (Qin et al, 2015) but not likely salinity (Wuchter et al, 2004(Wuchter et al, , 2005. Although the effects of these environmental parameters on OH-GDGT cyclization have not been rigorously tested, emerging evidence suggests that salinity, sea ice, seasonality, and terrestrial input may be complicating factors in some oceanic settings (Fietz et al, 2013;Kang et al, 2017;Lü et al, 2019;Park et al, 2019;Wei et al, 2020;Sinninghe Damsté et al, 2022).…”
Section: Gdgtsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to temperature, recent studies have shown that several other environmental and geochemical factors can influence the degree of GDGT cyclization, such as growth phase (Elling et al, 2014), ammonia oxidation rates (Hurley et al, 2016), and oxygen concentrations (Qin et al, 2015) but not likely salinity (Wuchter et al, 2004(Wuchter et al, , 2005. Although the effects of these environmental parameters on OH-GDGT cyclization have not been rigorously tested, emerging evidence suggests that salinity, sea ice, seasonality, and terrestrial input may be complicating factors in some oceanic settings (Fietz et al, 2013;Kang et al, 2017;Lü et al, 2019;Park et al, 2019;Wei et al, 2020;Sinninghe Damsté et al, 2022).…”
Section: Gdgtsmentioning
confidence: 99%
“…However, BAYSPAR does not include surface sediment for sensitive oceanographic regions like Baffin Bay (Tierney and Tingley, 2014). For this reason, developing local correlation-constrained calibrations can be particularly useful to capture the nuances of oceanographic variability in regions where global dataset coverage is lacking or where the temperature relationship deviates from global linear calibrations (e.g., Harning et al, 2019;Park et al, 2019;Fietz et al, 2020;Sinninghe Damsté et al, 2022). Moreover, exploring the potential influence of additional environmental variables (e.g., salinity, DO, nutrients) will help us better understand the mechanisms behind (and functionality of) this commonly applied paleotemperature proxy.…”
Section: Temperature Calibrationsmentioning
confidence: 99%
“…Sinninghe Damsté, Warden, et al. (2022) also noted higher RI‐OH values in lake sediments than marine sediments in several Baltic Sea sediment cores and attributed them to the effect of salinity. Recently, Xiao et al.…”
Section: Resultsmentioning
confidence: 93%
“…Sinninghe Damsté, Warden, et al (2022) also noted higher RI-OH values in lake sediments than marine sediments in several Baltic Sea sediment cores and attributed them to the effect of salinity. Recently, Xiao et al (2023) and Varma et al (2024) both found an unusually large range of RI-OH values in tropical oceans and attributed it to the effect of water depth.…”
Section: Comparison Of Ri-oh Between Lacustrine and Marine Settingsmentioning
confidence: 88%
“…All the original data have been deposited publicly to the repository of Zenodo (https://doi.org/10.5281/zenodo.7114938). All the supporting data can be found in the cited references (Chen et al., 2020; Davtian & Bard, 2023; Davtian et al., 2019, 2021; Fietz et al., 2013, 2016; Huguet et al., 2013; Kaiser & Arz, 2016; Kremer et al., 2018; Lamping et al., 2021; L. Liu et al., 2022; Lü et al., 2015; Morcillo‐Montalba et al., 2021; Sinninghe Damste et al., 2022; Wei et al., 2020; Yang, 2017; Yang et al., 2018).…”
Section: Data Availability Statementmentioning
confidence: 99%